Teologi Toleransi Agama Khonghucu di Klenteng Boen Bio Surabaya - M Thoriqul Huda (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2019)
Mutual respect and mutual appreciation is an attitude that must be possessed by everyone to realize tolerance. Tolerance is the most important aspect of living in a community. Where in living in society, of course, everyone wants a life that is safe, peaceful and peaceful. However, it is undeniable that many differences will be found in society, ranging from the nature, behavior, culture, ethnicity, even different religions of others. Differences can lead us to two opposite things, namely hostility and peace. Differences can be hostile if we cannot respond to differences themselves, and can truly be peaceful if we can accept and respect these differences. Many religious differences cause conflict, but today many religious people are aware of differences and begin to instill tolerance within themselves. As in Confucianism, this ethnic Chinese religion also upholds tolerance. This is done on the grounds that differences do exist and differences are not to destroy each other but to complement. Like the Confucian religion in Indonesia, they appreciate diversity. Chinese ethnicity is aware that Indonesia is a diverse country, and Indonesia was born from these differences. That proves that differences bring unity, not even bring destruction. In Confucianism, it was also taught about tolerance, which was later implicated in community life which was full of diversity. For example, in the Boen Bio temple area in Surabaya, they respect, respect and understand each other with the surrounding community who have different beliefs with them.